Pemberdayaan Tenaga Kesehatan dan Kader dalam Pelayanan Kegawatdaruratan Maternal dan Neonatal yang Excellent di Desa Bangun Rejo Kabupaten Deli Serdang Provinsi Sumatera Utara - Marta Armita Silaban; Vitalia Hanako Simanjuntak; Eva Dona Sinaga; Sari Simanjuntak; Sarah Sausan (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Neonatal maternal emergencies are a contributing cause of maternal mortality, including hypertension disorders, namely preeclampsia/eclampsia (33.07%), obstetric hemorrhage (27.03%), other obstetric complications 12.04%, infections in pregnancy (6.06%) (Indonesian Ministry of Health, 2019). Maternal mortality and morbidity can actually be reduced or prevented with various improvements in the field of obstetric health services. In Indonesia, obstetric emergency problems occur due to four delays, namely being late in recognizing danger signs and risks, being late in making a decision to seek help, being late in getting transportation to reach a more capable health service facility, and being late in getting help at a referral facility. Bangun Rejo Village is one of the villages in the Tanjung Morawa Community Health Center which has the highest risk of pregnant women compared to other villages. Involvement in decision making regarding referrals is still predominantly obtained from the family, so that family knowledge regarding emergency problems and pregnancy complications experienced by the mother greatly influences the accuracy of decision making to refer/contact a midwife/health worker so that treatment can be obtained more quickly. This activity aims to increase the knowledge of health workers, namely village midwives and cadres, in providing excellent maternal and neonatal emergency services in Bangun Rejo Village. This activity was attended by 9 midwives and 11 cadres from 11 hamlets in Bnagun Rejo Village. The results of this activity were that there was an increase in partners' knowledge before and after the intervention in the "good" category, which increased by 53% and in the "poor" category, which decreased by 53%. The initial pretest score was 45% which increased in the post test to 98%. It is necessary to increase the knowledge and abilities of village midwives and cadres in Bnagun Rejo Village regarding maternal and neonatal emergency services.